Means of visual activity of video art: Kharkiv projects "In the Dark" and "Fierce" - Logachova, Bella (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article examines the use of moving image and video practices as a means of visual activity in the cultural and artistic exhibition environment. The analysis is based on the influence of the visual in the context of social and contemporary art. This problem is raised in the theory of Ukrainian art criticism about Ukrainian video art in a visual way and represents the testing of art projects. The aim is to analyze and define the segments of visual activity of Kharkiv video art using the examples of the projects In the Dark and Liutyi. The analysis of sources and recent publications has revealed a high degree of research on the emergence of video art and the reasons for the emergence of a new screen form in the global context, but in the context of the contemporary development of Ukrainian video art and the peculiarities of the use of moving image in the practices of Ukrainian artists at the level of local and regional schools, it has not been properly and deeply studied. The artistic direction of video art, which emerged at the turn of the twentieth and twenty-first centuries, has not received structuring and theorization of the main technical and technological means of reproduction and representation of forms and hybrid forms, including a study of the artistic practices of Kharkiv video art and its place in the general context of the regional peculiarities of Ukrainian video art. The study of these issues and the development of these principles are the most relevant issues for the Ukrainian artistic process. It is important to note that art projects such as In the Dark and Liutyi, which use video art, have a common idea, a common space and environment. They develop the aesthetics of a loft space for immersion in a new reality that creates a moving image and is also part of the contemporary creative industry. Artistic visions change the viewer’s emotions and mental component into a transformed sense of reality, causing a state of immersion, combining different and distant associations in one trope and leading to a synthesis of several sensations, which actualizes the personal, visual and deepens the social sense of the individual.